Transport mechanisms in a puckered graphene-on-lattice. Issue 16 (11th April 2018) - Xu, T.; Díaz Álvarez, A.; Wei, W.; Eschimese, D.; Eliet, S.; Lancry, O.; Galopin, E.; Vaurette, F.; Berthe, M.; Desremes, D.; Wei, B.; Xu, J.; et al.
Abstract : Nanoscale study of the chemical interaction versus strain in a suspended graphene monolayer on SiO2 nanopillar arrays for higher piezoresistive sensitivity. Abstract : Understanding the fundamental properties of graphene when its topography is patterned by the use of a compliant substrate is essential to improve the performances of graphene sensors. Here we suspend a graphene monolayer on SiO2 nanopillar arrays to form a puckered graphene-on-lattice and investigate the strain and electrical transport at the nanoscale. Despite a nonuniform strain in the graphene-on-lattice, the resistivity is governed by thermally activated transport and not the strain. We show that the high thermal activation energy results from a low charge carrier density and a periodic change of the chemical potential induced by the interaction of the graphene monolayer with the nanopillars, making the use of graphene-on-lattice attractive to further increase the electrical response of graphene sensors.